Chem Differential Eq HW Solutions Fall 2011 13

Chem Differential Eq HW Solutions Fall 2011 13 - F , you...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Section 2.3 Fourier Series of Functions with Arbitrary Periods 13 33. The function F ( x ) is continuous and piecewise smooth with F ± ( x )= f ( x ) at all the points where f is continuous (see Exercise 25, Section 2.1). So, by Exercise 26, if we differentiate the Fourier series of F , we get the Fourier series of f . Write F ( x )= A 0 + ± n =1 ² A n cos p x + B n sin p x ³ and f ( x )= ± n =1 ² a n cos p x + b n sin p x ³ . Note that the a 0 term of the Fourier series of f is 0 because by assumption ´ 2 p 0 f ( x ) dx = 0. Differentiate the series for F and equate it to the series for f and get ± n =1 ² - A n p sin p x + p B n cos p x ³ = ± n =1 ² a n cos p x + b n sin p x ³ . Equate the n th Fourier coefficients and get - A n p = b n A n = - p b n ; B n p = a n B n = p a n . This derives the n th Fourier coefficients of F for n 1. To get A 0 , note that F (0) = 0 because of the de±nition of F ( x )= ´ x 0 f ( t ) dt .So 0= F (0) = A 0 + ± n =1 A n = A 0 + ± n =1 - p b n ; and so A 0 = n =1 p b n . We thus obtained the Fourier series of F in terms of the Fourier coefficients of f ; more precisely, F ( x )= p π ± n =1 b n n + ± n =1 ² - p b n cos p x + p a n sin p x ³ . The point of this result is to tell you that, in order to derive the Fourier series of
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: F , you can integrate the Fourier series of f term by term. Furthermore, the only assumption on f is that it is piecewise smooth and integrates to 0 over one period (to guarantee the periodicity of F .) Indeed, if you start with the Fourier series of f , f ( t ) = ∞ ± n =1 ² a n cos nπ p t + b n sin nπ p t ³ , and integrate term by term, you get F ( x ) = µ x f ( t ) dt = ∞ ± n =1 ² a n µ x cos nπ p tdt + b n µ x sin nπ p tdt ³ = ∞ ± n =1 ² a n ¶ p nπ · sin nπ p t ¸ ¸ ¸ x dt + b n ¶-p nπ · cos nπ p t ¸ ¸ ¸ x ³ = p π ∞ ± n =1 b n n + ∞ ± n =1 ²-p nπ b n cos nπ p x + p nπ a n sin nπ p x ³ , as derived earlier. See the following exercise for an illustration....
View Full Document

This note was uploaded on 12/22/2011 for the course MAP 3305 taught by Professor Stuartchalk during the Fall '11 term at UNF.

Ask a homework question - tutors are online